2012
DOI: 10.1111/j.1365-2621.2011.02909.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal conditions for the production of monoacylglycerol from crude palm oil by an enzymatic glycerolysis reaction and recovery of carotenoids from the reaction product

Abstract: Summary Monoacylglycerol (MAG) was produced from crude palm oil (CPO) by the enzymatic glycerolysis reaction in organic solvents. The optimal conditions for MAG production from CPO were: the use of a mixture of tert‐butanol and hexane (1:1) as the organic solvents; an immobilised lipase of 40%; a molar ratio of glycerol to CPO of 8:1 with 4% of water content in the glycerol; and an initial CPO concentration of 10%. A maximum yield of 74.3% MAG was obtained with an initial production rate of 42.3 mg MAG mL−1 h−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
10
0
3
Order By: Relevance
“…To investigate the effect of the enzyme concentration on the conversion of methyl laurate, a number of experiments with various enzyme dosage (1∼9 wt.%) were performed. As displayed in Figure 4, the conversion of methyl laurate increased rapidly with lipase concentration increasing in the range of 1∼7 wt.%, which could be due to the increase in the concentration of catalyst causing an increase in the collision frequency with the reactants [17]. At 7 wt.%, the conversion reached 60%.…”
Section: Effect Of Enzyme Concentrationmentioning
confidence: 90%
“…To investigate the effect of the enzyme concentration on the conversion of methyl laurate, a number of experiments with various enzyme dosage (1∼9 wt.%) were performed. As displayed in Figure 4, the conversion of methyl laurate increased rapidly with lipase concentration increasing in the range of 1∼7 wt.%, which could be due to the increase in the concentration of catalyst causing an increase in the collision frequency with the reactants [17]. At 7 wt.%, the conversion reached 60%.…”
Section: Effect Of Enzyme Concentrationmentioning
confidence: 90%
“…The study stated that the intraparticle diffusion rate of ß-carotene was improved by increasing the temperature to 50 • C, and a temperature beyond 50 • C was not desirable because of the heat-sensitive properties of ß-carotene. Several studies of carotenoids adsorption indicated that the optimal temperature of carotenoid adsorption was between 50 and 60 • C (Baharin et al, 1998;Latip et al, 2001;N. Majid & Cheirsilp, 2012;Muhammad et al, 2013;Ulfah et al, 2017).…”
Section: Adsorptionmentioning
confidence: 99%
“…Majid & Cheirsilp, 2012;Muhammad et al, 2013;Ulfah et al, 2017). Sometimes, a slightly higher operating temperature (50 to 65 • C) was advantageous because the viscosity of palm oil could be reduced while preserving the phytonutrients like squalene, carotenoids, and tocols (Baharin et al, 1998 N. Majid & Cheirsilp, 2012;Muhammad et al, 2013;Ulfah et al, 2017).…”
Section: Adsorptionmentioning
confidence: 99%
“…Previous literature has shown that functional groups play more critical roles than solvent polarity in enzymatic reactions. All solvent molecules in both tert-butanol/iso-propanol and tert-butanol/tert-pentanol systems have alcoholic hydroxyl groups, which may play a crucial role in the entry of substrates into the active site of the enzyme 19 .…”
Section: Screening Of Binary Solventsmentioning
confidence: 99%